Purchase Intention: Pengaruh Price Discount, Bonus Pack Dan Celebrity Endorser - Meilaty Finthariasari; Adithya Melano Zetira (Faculty of Economics and Business University of Lampung, 2022)
This study aimed to determine the effect of price discount, bonus pack, and celebrity endorser toward purchase intention of Moy Stuff online Shop in Bengkulu City. The sample of this research was 180 people of Moy Stuff online shop Consumers in Bengkulu City. This study used observation and questionnaires as techniques for collecting data. Several data analysis techniques were used in this research, including using instrument test, classical assumption test, respondent analysis, multiple linear regression analysis, determinant coefficient, and hypothesis testing. The results of the tests show that the variable price discount (X1), bonus pack (X2), celebrity endorser (X3) have a partial and simultaneous effect on purchase intention on Moy Stuff online shop in Bengkulu city. From the results of the multiple linear regression test, the regression equation is Y= 0.521 + 0.294 (X1) + 0.135 (X2) + 0.459 (X3). Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh diskon harga, paket bonus, dan celebrity endorser terhadap niat beli online shop Moy Stuff di Kota Bengkulu. Sampel penelitian ini adalah 180 orang Konsumen online shop Moy Stuff di Kota Bengkulu. Penelitian ini menggunakan observasi dan angket sebagai teknik pengumpulan data. Teknik analisis data yang digunakan dalam penelitian ini antara lain dengan menggunakan uji instrumen, uji asumsi klasik, analisis responden, analisis regresi linier berganda, koefisien determinan, dan pengujian hipotesis. Hasil pengujian menunjukkan bahwa variabel diskon harga (X1), paket bonus (X2), celebrity endorser (X3) berpengaruh secara parsial dan simultan terhadap niat beli online shop Moy Stuff di kota Bengkulu. Dari hasil uji regresi linier berganda diperoleh persamaan regresi adalah Y= 0,521 + 0,294 (X1) + 0,135 (X2) + 0,459 (X3). Kata kunci: Diskon Harga, Paket Bonus, Endorser Selebriti, Purchase Initention